Moral Education Values in the Al-Qur'an and Their Relevance to the Character Formation of Students - Purwanti, Eny Ratna; Pusparini; Maimunah; Benny Prasetiya (Education Reserach Center, 2026)
Moral education in the Al-Qur’an is the primary foundation in shaping the character of human beings who are faithful, civilized, and responsible. Amid the development of globalization, digitalization, and the moral crisis affecting the educational world, strengthening moral values has become an urgent necessity within the Islamic educational system. This study aims to analyze the values of moral education in the Al-Qur’an and their relevance to the character formation of students in the context of contemporary education. This research employs a qualitative approach based on library research using thematic analysis and contextual hermeneutics toward Al-Qur’anic verses related to morality. The primary data sources consist of the Al-Qur’an and classical as well as contemporary tafsir literature, while the secondary data sources include scientific journals, academic books, and relevant previous studies. The findings reveal that the values of moral education in the Al-Qur’an include honesty, responsibility, compassion, discipline, tolerance, justice, and self-control. These values possess very strong relevance to the character formation of students, especially in facing the challenges of the digital era characterized by declining social ethics and increasing individualism. This study confirms that Al-Qur’anic moral education functions not only as spiritual guidance but also as an integrative and humanistic paradigm of character education in building generations with noble personalities.